Low sulfur, phosphorus and metal free antiwear additives: Synergistic action of salicylaldehyde N(4)-phenylthiosemicarbazones and its different derivatives with Vanlube 289 additive - Rastogi R.B.; Maurya J.L.; Jaiswal V. (My University, 2025)
With a view to develop metal free, low SAPs antiwear additives, the antiwear properties of salicylaldehyde N(4)-phenylthiosemicarbazone and its p-methylphenyl, p-methoxyphenyl and p-chlorophenyl derivatives(1w/v) and their synergistic/antagonistic behavior with Vanlube 289(1w/v) additive were tested in base oil using four-ball lubricant tester and ZDDP as a reference additive. Antiwear testing of additives(1w/v) was done by varying load and time. The performance of antiwear additives has been compared on the basis of tribological parameters. An appreciable synergistic activity is observed between 1 concentrations of the thiosemicarbazones and Vanlube289. The efficiencies of the synergistic formulations are far better than that of ZDDP. The topography and composition of the wear scar were analyzed by AFM and SEM with EDX. The synergistic formulations cause enormous reduction in surface roughness. The EDX analysis of the wear scar in the case of base oil with additive exhibits presence of sulfur and nitrogen. © 2012 Elsevier B.V.